(The military role of the Kurdish tribes in the Levant Countries during the first thirty years of the rule of the Bahri Mamluk state (648- 678 Hijra/ 1250- 1279 AD - Alamayreh, Mohammad Abdullah (Journal of Humanities & Social Sciences, 2020)
This research aims to study the military role of the Kurdish tribes in the Levant Countries during the first 30 years of the rule of the Mamluk state (648- 678 hijra/ 1250- 1279 AD (. The two great dangers represented by the Mongol invasion of the eastern Muslim world, and the danger of the Franks in the remaining Franjian emirates and cities in the Levant Countries. The difficult circumstances which was imposed on the early Sultans forced them to benefit from the state of chaos which was created by the Mongols after their subjugation of the Ayyubid Emirates in the Levant Countries. Those Sultans joined the remnants of the Ayyubid armies, which were formed from the Turks, Kurds and Turkmen, to their armies to face these dangers. The Kurdish tribal groups, which practiced fighting in the most difficult circumstances, played a major role in the Mamluks' victorious wars against the Mongols and Franks.This research reveals this role as a contribution to the study of the human structure of the Mamluk army in that period.
Keywords: the Mamluks; the Kurds; the Levant; al-Zahir Baybars